Low concentrations of cytokines produced by allergen-stimulated peripheral blood mononuclear cells have potent effects on nasal polyp-derived fibroblasts - OLSSON, S (Blackwell Science Inc, 2003)
Accumulating data show that fibroblasts are important regulators in the development and maintenance of allergic airway inflammation. However, most studies so far have used individual recombinant cytokines in high concentrations, unlikely to be found in vivo. We aimed to investigate how cytokines produced by peripheral blood mononuclear cells (PBMC) affect fibroblast functions. Primary airway fibroblasts where incubated with allergen-stimulated or non-stimulated PBMC supernatants from allergic patients. The levels of cytokines in PBMC supernatants were measured and the expression of CD54, CD40 and CD106 as well as the production of eotaxin, interleukin (IL)-6 and IL-8 were assessed in fibroblasts. Although the levels of single cytokines measured in PBMC supernatants were low, a significant up-regulation of the surface molecules as well as of IL-6 and IL-8 production was found in fibroblasts cultured with allergen-stimulated PBMC supernatants as compared to non-stimulated, while the increase in eotaxin production was not significant. The evaluation of correlations between cytokines produced by PBMC and effects seen on fibroblasts did not indicate a crucial role for any single cytokine. Furthermore, the addition of comparably low concentrations of recombinant interferon (rIFN)-γ or recombinant tumour necrosis factor (rTNF)-α did not induce the same effects as PBMC supernatants, the only exception being TNF-α as a direct inducer of CD54 expression. Our results show that synergistic mechanisms has a more important role than single mediators, highlighting important differences between in vitro experiments, where effects of individual mediators are studied, versus the actual situation in vivo.